The Emergence of the Fairy Tale Genre; Artistic and Compositional Signs of Fairy Tales (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article discusses the specific features of the genesis of the fairy tale genre, and at the same time, fairy tales serve as an important source for studying the history of each nation. When working on a fairy tale, it is important to teach children not only to read a fairy tale, but also to tell it. Telling stories develops oral speech, enriches children’s speech with new words and phrases.